ANALISIS NILAI-NILAI RELIGIUS ASPEK BERSYUKUR DALAM NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY - Dewi Sapriani; Erlina Zahar; Harbeng Masni (Universitas Batanghari, 2018)
This research is intended to describe the aspect of grateful between human and God (Hablumminallah) which is found in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy. This research is qualitative descriptive. It is used to describe the aspect of grateful of God’s grace in the novel Bidadari Bermata Bening karya by Habiburrahman El Shirazy.Basen on the analysis, it can be seen that there some aspects found, they are: there are 36 quotes of the aspect of grateful of Allah’s blessing. This thing represents how human learns to be grateful with what God has given in their life. Based on the analysis, it can also be concluded that the novel Bidadari Bermata Beningby Habiburrahman El Shirazy contains the religious value which is related with human relationship with God (Hablumminallah) from the perspective of God’s grace to human being. Key Words:religious value, grateful aspect, novel Bidadari Bermata Bening